2017
DOI: 10.1136/bmjopen-2017-017557
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in tuberculosis patients with diabetes, prediabetes and normal blood glucose in China: a cross-sectional study

Abstract: ObjectiveThe association between tuberculosis (TB), diabetes mellitus (DM) and vitamin D status is poorly characterised. We therefore: (1) determined vitamin D status in patients with TB in relation to whether they had normal fasting blood glucose (FBG), pre-DM or DM and (2) assessed whether baseline characteristics in patients with TB, including their DM status, were associated with vitamin D deficiency.MethodsIn patients with TB consecutively attending six clinics or hospitals in China, we measured 25-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…Fourth, we did not find associations between vitamin D deficiency and baseline characteristics such as age, gender, residential community and number of daily cigarettes smoked, findings also in line with previous research [ 14 ]. Contrary to previous research [ 14 , 28 ], we found no strong association in this study with season, possibly because most of our patients lived in urban areas which may not have been so affected by reduced nutritional intake that occurs in the winter time. In the previous report, 32.5% of the study population resided in urban areas, but the figure was 50.0% in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Fourth, we did not find associations between vitamin D deficiency and baseline characteristics such as age, gender, residential community and number of daily cigarettes smoked, findings also in line with previous research [ 14 ]. Contrary to previous research [ 14 , 28 ], we found no strong association in this study with season, possibly because most of our patients lived in urban areas which may not have been so affected by reduced nutritional intake that occurs in the winter time. In the previous report, 32.5% of the study population resided in urban areas, but the figure was 50.0% in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Both DM and TB are associated with malnutrition and this association may be stronger with a longer duration of DM and multiple episodes of TB [ 32 ]. Amongst our study group, the proportion with older age and retreatment TB at nearly 30% was higher than found in a previous study of TB patients [ 14 ], a finding similar to that observed in Guangzhou [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was a prospective cohort study that recruited patients registered with TB at six clinics within the routine TB services in Jilin Province between November 2015 and July 2016 and followed them up until they all could have completed anti‐TB treatment. Details of the setting and sites, sample size, patient inclusion, blood sample collection and vitamin D measurements have been published elsewhere . Persons over the age of 18 years were consecutively recruited directly after the diagnosis of TB was recorded with no specific repeat in medical history or examination made.…”
Section: Methodsmentioning
confidence: 99%